Gastric Tissue Selenium Levels in Healthy Persons, Cancer and Non-Cancer Patients with Different Kinds of Mucosal Damage - Burguera, J.L.; Villasmil, L.M.; Burguera, M.; Carrero, P.; Rondon, C.; De Abel De La Cruz, A. Matousek; Brunetto, M.R.; Gallignani, M. (Journal of trace elements in medicine and biology, 1995)
The gastric tissue levels of selenium (Se) were examined in 15 healthy subjects aged 18-43 (mean 36 ± 12) years, 17 patients with stomach cancer aged 23–79 (mean 60 ± 17) years, 20 patients with mild gastritis aged 18–65 (mean 35 ± 12) years, 13 patients with chronic gastritis aged 28–69 (mean 47± 15) years, 33 patients with erosive gastritis aged 16–70 (mean 49 ± 17) years and 23 patients with ulcers aged 22–76 (mean 49 ± 17) years. The Se concentration was determined by electrothermal atomic absorption spectrometry (ETAAS) with palladium as a matrix modifier. The mean ± the standard deviation (SD) of the gastric tissue Se levels were 473 ± 80, 36 ± 9.0, 355 ± 243, 567 ± 246, 571 ± 241 and 813 ± 427 μg/Kg in healthy subjects and in patients with cancer, ulcers, mild gastritis, chronic gastritis and erosive gastritis, respectively. The Se concentration in the biopsies of patients with gastric ulceration and cancer were significantly lower than that in patients with gastritis (p< 0.05) and the other conditions (p < 0.0001).